European standards for the functioning of places of detention and their significance for Ukraine - Sukhorab, Ruslan (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
This article analyzes and studies the issue of European standards for the functioning of places of detention, as well as their impact on Ukrainian realities in the field of protection of the rights of persons held in such places. It is proved that the development of democratic institutions, strengthening of human rights, and combating violations in the penitentiary system require the study and implementation of European standards. It is emphasized that after the Revolution of Dignity in 2014, Ukraine began reforming the penitentiary system. However, many problems remain relevant, including, in particular, overpopulation of penitentiary institutions; outdated infrastructure that does not meet modern requirements; underfunding and low staff remuneration; insufficient attention to the psychological and social rehabilitation of convicts. When studying the issue of standards in the field of functioning of places of detention, we believe that they are formed by the following three mechanisms: first, international standards for the treatment of convicts and prisoners, usually called “international penitentiary standards”. Secondly, case law plays an important role, in particular the decisions of the European Court of Human Rights (ECHR). Thirdly, it is worth noting the monitoring activities carried out through the reports of the European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment. After analyzing each of these elements, it was concluded that European standards, such as the European Convention on Human Rights, the Council of Europe’s Recommendations on Prison Conditions and Re-socialization, the case law of the European Court of Human Rights, and the case law of the European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment, are the basis for improving the system of places of detention. Ukraine, as a signatory to numerous international agreements, is obliged to implement them in national legislation and practice.